2012
DOI: 10.1103/physrevlett.109.245005
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Attosecond Pulses from Laser-Driven Synchrotron Radiation

Abstract: A quantitative theory of attosecond pulse generation in relativistically driven overdense plasma slabs is presented based on an explicit analysis of synchrotron-type electron trajectories. The subcycle, field-controlled release, and subsequent nanometer-scale acceleration of relativistic electron bunches under the combined action of the laser and ionic potentials give rise to coherent radiation with a high-frequency cutoff, intensity, and radiation pattern explained in terms of the basic laws of synchrotron ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 27 publications
2
46
0
Order By: Relevance
“…The stored energy in these nanobunches couples efficiently into radiative electromagnetic modes through a process similar to that of the well known synchrotron emission and thus generates harmonics. 22,[25][26][27][28] This process is called CSE. In addition to the laser intensity and plasma scale length dependence, conditions for CSE harmonics in specular direction have also been mentioned to depend on angle of incidence, laser pulse duration, and carrier envelope phase; 22 although no detailed investigation on the influence of these parameters has been performed.…”
Section: Introductionmentioning
confidence: 99%
“…The stored energy in these nanobunches couples efficiently into radiative electromagnetic modes through a process similar to that of the well known synchrotron emission and thus generates harmonics. 22,[25][26][27][28] This process is called CSE. In addition to the laser intensity and plasma scale length dependence, conditions for CSE harmonics in specular direction have also been mentioned to depend on angle of incidence, laser pulse duration, and carrier envelope phase; 22 although no detailed investigation on the influence of these parameters has been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Similar oscillations have been noticed in Ref. [17]. In contrast to the opaque case, the net layer displacement at the end of the interaction of the pulse with the layer is not small and provides the initial condition for the "sawtooth" oscillations that are a periodic sequence of hyperbolic motions of the electric charge in the homogeneous electric field [36] due to the ion layer.…”
Section: B Transparent Mirrormentioning
confidence: 57%
“…[6,9]. These features provide novel regimes for ion acceleration [10][11][12][13][14], relativistic high order harmonics generation [15][16][17], light frequency upshifting [20][21][22][23][24][25][26], and laser pulse shaping [9,[27][28][29][30][31]. They become important when the foil thickness is shorter than, or of the order of, both the laser wavelength and the plasma collisionless skin depth.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its superior properties and predominance at high intensities, the basis for the generation of single asec light pulses [87,119] will most probably be the ROM mechanism. More recently, theoretical work has revealed that, under certain conditions, another mechanism can dominate and produce harmonic radiation with superior efficiency [120][121][122][123][124][125]. In this mechanism dense electron nanobunches are formed at the plasma vacuum boundary giving rise to XUV radiation by coherent synchrotron emission (CSE).…”
Section: Xuv Emission From Solid Surfacesmentioning
confidence: 99%